(untitled) (Revista Médica de Trujillo, 2025)
Objetive: To determine whether there is an association between the existence of predisposing clinical characteristics and the presence of intraoperative complications of phacoemulsification, and between the presence of complications and final visual acuity in patients diagnosed with cataracts, who were operated on 2019 at an Ophthalmology Institute. Methods: Analytical observational study in a retrospective cohort, having reviewed 1,561 medical records; 1,174 were excluded because they corresponded to patients with systemic or ocular comorbidities that could affect the visual out come, and 387 records were included, in which it was found that 156 patients had undergone surgery on both eyes (312 surgeries) and 231 on one eye only, leaving 543 surgeries to be analyzed. The frequency of predisposing clinical characteristics and the presence of intraoperative complications were determined, and an association between them was sought (first phase); The frequency of complications was then related to visual acuity one month after surgery (second phase). Results: the mean age was 69,5 ± 8,5 years, and 52,4 % were men. Capsular pseudoexfoliation and pupillary dilation < 6 mm were the most frequent predisposing clinical characteristics in surgeries with intraoperative complications (p < 0,050). The frequency of complications was 7 %, with posterior capsule rupture predominating (3,8 %). Post-operative best corrected visual acuity (BCVA) was significantly lower in the presence of complications (p = 0,014; however, visual success (BCVA better than 20/60) was achieved in 36 of the 38 complicated cases. Conclusion: The frequency of complications was 7 %, with posterior capsule rupture predominating. An association was found between the presence of capsular pseudoexfoliation and pupillary dilation equal to or less than 6 mm and the frequency of complications. Final visual acuity better than 20/60 was achieved in 94,7 % of patients with complications and in 99,8 % of those without complications, p = 0,014.